THE IMPLEMENTATION OF KESBANGPOL AND KPUD POLITICAL SOCIALIZATION ACTIVITIES IN THE CITY OF PEKANBARU ON BEGINNING VOTERS (WHICH HAS NEW KTP) IN THE 2019 ELECTION - Krisdy, M. Irsyad; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The holding of direct, public, free, secret, honest and fair elections will have a positive impact on strengthening democracy both at the local and national levels. The public is given the right to vote for candidates, as well as political parties whose value individuals will be able to fight for their aspirations if they are elected later in the election. Voters are required to be smart to be able to choose and assess properly and carefully who are the people's representatives who are appropriate and can fight for their aspirations. This means that voters must have a good knowledge of their rights and obligations in the election so that there is a growing awareness of the importance of participating in elections, especially for novice and retired voters. The purpose of this study was to determine and analyze the Comparison of the Socialization of Kesbangpol and KPUD City on Beginner Voters (Newly Having KTP and Retired Officers) in the 2019 Election and its obstacles. This research was conducted with a qualitative type with informants, namely the head of Kesbangpol, the head of the KPUD and novice and retired voters. The results of this research are the Socialization of Kesbangpol and KPUD of Pekanbaru City to Beginner Voters (Those Who Have New KTPs and Retired Officers) In the 2019 Election it has not been optimal and on target which is expected to increase voter participation, especially beginners so that they can give their voting rights for the betterment of the nation. and this Country. The reason for the low participation of first-time voters in Pekanbaru City at the time of the 2019 Mayor and Deputy Mayor Election is the failure of the General Election Commission to function properly. The function of the General Election Commission has not been running properly due to the uneven socialization carried out by the KPU and Kesbangpol Pekanbaru City.  Keywords: Implementation, Socialization, General Election